Demystifying the Role of Technological Entrepreneurship on the Performance of Medium-Scale Enterprises (MSEs) - ADETOWUBO-KING , Sunday Adetayo; OLATOYE , Adeolu Oludare; OLADIPO , Oluwaseyi Temilade (Covenant Journal of Entrepreneurship, 2024)
This study delves into the impact of technological entrepreneurship on Micro and Small Enterprises (MSEs) in Lagos, Nigeria, shedding light on how integrating technological entrepreneurship into business operations can unlock opportunities for improved product or service quality, sales growth, and profitability. Conversely, it reveals that non-technological entrepreneurial activities may hinder MSEs' entrepreneurship and productivity. Employing a mixed research approach, combining primary and secondary data, the study employs descriptive and inferential statistics, including panel regression analysis and correlation coefficients, to assess the implementation of technological entrepreneurship and its effect on business performance. Notable findings pinpoint factors influencing technological entrepreneurship implementation, such as Business Size, Perceived Ease of Use, Cost of Technology Deployment, Perceived Benefit, Market Dynamism, and Business Environment, all significantly impacting business performance. Identified obstacles to technological entrepreneurship implementation include Inconsistency in Government Policy, Lack of Proper IT Proficiency, Fear of Data Insecurity, High Cost of Technology Deployment, and Legacy Culture Thinking. The study concludes that technological entrepreneurship significantly propels MSEs' performance in Lagos and urges entrepreneurs to bolster their technological capacity for heightened productivity. Moreover, it underscores the social implications, such as the potential for job creation, economic growth, and heightened competitiveness within the MSE sector, emphasizing the pivotal role of entrepreneurs in advancing both business performance and broader societal development.